The Main Pests Of Seed Orchards Of Surkhandarya Region - Tojiyeva Feruza Anvarovna (Zien Journals, 2024)
This thesis includes Cydia pomonella ( Linnaeus, 1785), an apple orchard belonging to the family Tordicidae, which is widespeared in orchards and harms them; The distribution, damage, and bioecological characteristics of the California shield Diaspidiotus perniciosus (Coms, 1881) and the purple shield Parlotoria oleae (Colvee, 1880), which belong to the family Diaspididae, have been reported
Keywords: Malus domestica; Cydia pomonella; Grapholitha molesta; Parlotoria oleae